Implementasi Algoritma TEA dan Pontifex Dalam Keamanan Data File Dokumen - Saripah Aini (JURIKOM (Jurnal Riset Komputer), 2020)
Data security is one of the most important aspects in information technology. With a high level of security, hopefully the information presented can be maintained its authenticity. In this final project a system that secures data and information stored on the computer from cryptanalysts is formed. The steps that the author did to make the process of forming the system include the stages of problem analysis, algorithm and flowchart along with modeling the structure of the program and design of the application interface, so that the application formed becomes easy to use and has optimal functions. By using TEA and pontifex algorithms which are secret key cryptographic algorithms, these problems can be overcome. The strength of this algorithm lies in the feistel network (including substitution operations, permutations and modular arithmetic) and delta numbers derived from the golden number.